AUGMENTED REALITY (AR) AND VIRTUAL REALITY (VR) IN ENHANCING THE CONSUMER EXPERIENCE IN ECONOMY 5.0 - Caroline Caroline; Luckhy Natalia Anastasye Lotte; Redi Yana Kapisa (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Augmented Reality (AR) and Virtual Reality (VR) are innovative technologies that have great potential to improve the consumer experience in the Economy 5.0 era. Through AR and VR, consumers can interact with products and services in a more personal and in-depth way, enabling simulations and virtual experiences that reduce uncertainty and increase trust. In various industries, from retail to education and tourism, AR and VR create a more interactive and engaging environment, enriching the user experience and supporting more informed decisions. The implementation of this technology not only fulfils the practical needs of consumers, but also the emotional and cognitive aspects, supporting the creation of long-term relationships between brands and customers. Thus, AR and VR contribute to a more sustainable and human-centred economic ecosystem, in accordance with the principles of Economy 5.0.